Effects of a physical activity and nutrition program in retirement villages: A cluster randomised controlled trial - Jancey, Jonine; Holt, Anne-Marie; Lee, Andy; Kerr, Deborah; Robinson, Suzanne; Tang, Li; Anderson, A.; Hills, A.P.; Howat, Peter (Biomed Central, 2017)
Background: This cluster randomised controlled trial aimed to determine if a 6- month home-based intervention could improve the physical activity and dietary behaviours of adults aged 60 to 80 years living in retirement villages located in Perth, Western Australia. Methods: Participants (n = 363) from 38 retirement villages were recruited into the trial and allocated to the intervention (n = 197: 17 sites) or control (n = 166: 21 sites) group and were blinded. Previously validated instruments-Fat and Fibre Barometer and International Physical Activity Questionnaire, along with anthropometric measures (weight, height, waist and hip circumferences) and blood pressure were collected at baseline and 6 -month time period. Comparisons between intervention and control groups were undertaken pre- and post- intervention using univariate chi-square and t-tests. Multi-level mixed regression analyses were then conducted to ascertain the effects of the intervention on changes in the outcome variables over time and between groups. Results: A total of 139 (70.5%) intervention and 141 (84.9%) control group participants completed the program and post-test assessments. The intervention group demonstrated significant increases in time (80 min more per week on average) devoted to moderate-intensity physical activity, engagement in strength exercises (from 23.7% to 48.2%), frequency of fruit consumed as well as fat avoidance and fibre intake scores, in addition to a 0.5 kg mean reduction in weight post program, whereas no apparent changes were observed in the control group. Mixed regression results further confirmed statistically significant improvements in weight loss (p < 0.05), engagement in strength exercises (p < 0.001) and fruit intake (p = 0.012) by the intervention participants at post-test relative to their controls. Conclusions: Retirement offers a time to reassess lifestyle, and adopt positive health enhancing physical activity and dietary behaviours. This intervention was successful in improving weight, engagement in strength exercises, increasing levels of moderate-intensity physical activity and consumption of fruit among retirement village residents. Further investigation is needed on how to better engage retirement village managers in such programs. Trial registration: Australia and New Zealand Clinical Trial Registry (ACTRN12612001168842) registered November 2, 2012.